2020
DOI: 10.3329/jes.v11i1.49549
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Average Temperature Rise in Bangladesh: A Time Series Analysis

Abstract: Global warming has caused a significant increment in surface temperature around the world, including Bangladesh. In this study, the temperature data of Bangladesh over the past 100 years has been analyzed to see the temperature increment pattern. It has been seen that the average temperature has risen by 10C over the last century. Using daily average temperature data of Bangladesh, machine learning-based time series forecasting model has been developed to predict the future temperature of Bangladesh. The model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Dong, et al [21] enhanced short-term forecasting of daily precipitation using the XGBoost model combined with multi-factor bias correction for numerical weather prediction (NWP). Paul and Roy [22] developed a machine learning-based time series forecasting model to predict temperature any year in the future of Bangladesh.…”
Section: Related Workmentioning
confidence: 99%
“…Dong, et al [21] enhanced short-term forecasting of daily precipitation using the XGBoost model combined with multi-factor bias correction for numerical weather prediction (NWP). Paul and Roy [22] developed a machine learning-based time series forecasting model to predict temperature any year in the future of Bangladesh.…”
Section: Related Workmentioning
confidence: 99%
“…Their study indicated that climate change would cause continuous increases of rainfall, temperature and weather-related extreme events. Karmakar (2019) found patterns of climate change and its impacts in Future Projection of Mean Temperature ….. northwestern Bangladesh and in the very recent, Paul et al (2020) studied the past 100 years temperature data of Bangladesh and it found that in this period temperature of Bangladesh was risen by 1 0 C on average and an increment of close to another 1 0 C would be in the average temperature of Bangladesh from the prediction of the model in next century. Alamgir et al (2019) analyzed that the greatest increase in maximum and minimum temperature was found in the more northern regions and the lowest increase was found in the southeast coastal regions.…”
Section: Introductionmentioning
confidence: 99%